Statistical Survey of the Terrestrial Bow Shock Observed by the Cluster Spacecraft. Issue 3 (2nd March 2019) - Kruparova, O.; Krupar, V.; Šafránková, J.; Němeček, Z.; Maksimovic, M.; Santolik, O.; Soucek, J.; Němec, F.; Merka, J.
Abstract: The terrestrial bow shock provides us with a unique opportunity to extensively investigate properties of collisionless shocks using in situ measurements under a wide range of upstream conditions. Here we report a statistical study of 529 terrestrial bow shock crossings observed between years 2001 and 2013 by the four Cluster spacecraft. By applying a simple timing method to multipoint measurements, we are able to investigate their characteristic spatiotemporal features. We have found a significant correlation between the speed of the bow shock motion and the solar wind speed. We have also compared obtained speeds with time derivatives of locations predicted by a three‐dimensional bow shock model. Finally, we provide a list of bow shock crossings for possible further investigation by the scientific community. Plain Language Summary: The Sun is continuously emitting a stream of charged particles—called the solar wind—from its upper atmosphere. The terrestrial magnetosphere forms the obstacle to its flow. Due to supersonic speed of the solar wind, the bow shock is created ahead of the magnetosphere. This abrupt transition region between supersonic and subsonic flows has been frequently observed by the four Cluster spacecraft. Using a timing analysis, we have retrieved speed and directions of the bow shock motion for a large number of crossings. We have correlated the bow shock speed with the solar wind speed and predictions of the bow shock locations by the empirical model. A better understanding of the bow shock kinematics may bring new insights to wave‐particle interactions with applications in laboratory plasmas. Key Points: A significant correlation between the speed of the bow shock motion and the solar wind speed has been found Relative deviations from the model bow shock location are correlated with the bow shock speed The list of bow shock crossings observed by the four Cluster spacecraft between years 2001 and 2013 is provided as an Auxiliary material